Operational Planning of X-ray Screening Detection System: Feasibility Analysis, Capacity, and Service Process Analysis Approach - Safari, Jen Jen Mohammda; Indradewa, Rhian; Nugroho, Sukmo Hadi; Kustiawan, Unggul (Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the operational framework of PT. CKK in providing accurate and reliable security equipment repair and maintenance services through the integration of process design, technology, and supply chain management. Using a mixed approach involving case studies, document analysis, stakeholder interviews, field observations, and service flow simulations, the study developed a service blueprint that includes repair processes, preventive maintenance, and the application of technologies such as AI/Analytics for damage prediction, GPS-integrated CRM, blockchain for supply chain transparency, and custom testing tools. The results show that this strategy is able to optimize service efficiency, minimize operational downtime, and ensure compliance with international standards (TSA and ECAC). However, limitations such as the theoretical nature of the implementation of advanced technologies, reliance on the quality of historical data, and high investment burden need to be addressed. Managerial implications recommend strengthening data infrastructure, gradual technology adoption, e-learning-based HR training, supplier diversification, and expansion to the latest generation of security systems. This research provides practical guidance for security equipment maintenance service companies to improve service reliability while supporting market penetration in Indonesia through a combination of technical innovation and measurable operational management. The validation findings through limited simulations and focus group discussions also emphasized the importance of a balance between technological innovation and adaptation to operational limitations in the field